2015
DOI: 10.5713/ajas.14.0369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olive Leaf (<i>Olea europaea</i>) Powder on Laying Hens Performance, Egg Quality and Egg Yolk Cholesterol Levels

Abstract: This experiment was conducted to measure the effects of olive leaf powder on performance, egg yield, egg quality and yolk cholesterol level of laying hens. A total of 120 Lohmann Brown laying hens of 22 weeks old were used in this experiment. The birds were fed on standard layer diets containing 0, 1%, 2%, or 3% olive leaf powder for 8 weeks. Egg weight and yield were recorded daily; feed intake weekly; egg quality and cholesterol content at the end of the trial. Olive leaf powder had no effect on feed intake,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 24 publications
9
49
4
Order By: Relevance
“…Albumen weight is generally influenced by egg weight (Rajkumar et al, 2009). The averages of albumens weights in this research were lower than those reported by Cayan & Erener (2015) that albumen weight was 38.70 g (64.60%) and Mahmoud et al (2010) that albumen weight was 38.91 g.…”
Section: Physical Quality Of Eggcontrasting
confidence: 52%
See 3 more Smart Citations
“…Albumen weight is generally influenced by egg weight (Rajkumar et al, 2009). The averages of albumens weights in this research were lower than those reported by Cayan & Erener (2015) that albumen weight was 38.70 g (64.60%) and Mahmoud et al (2010) that albumen weight was 38.91 g.…”
Section: Physical Quality Of Eggcontrasting
confidence: 52%
“…The treatments did not affect eggshell weight. The average of eggshell weights in this research was higher than reported by Cayan & Erener (2015) that was 6.63 g (11.00%). According to Yoon et al (2015), piperine powder will inhibit the activity of Ca 2-ATP-ase enzyme in transporting the calcium ions across the cell membrane that will decrease calcium.…”
Section: Physical Quality Of Eggcontrasting
confidence: 52%
See 2 more Smart Citations
“…Bioactive molecules (mainly polyphenols) in EVOO support positively the reduction of pathogens that might increase in the digestive system of poultry, while reducing the toxins formation in the feedstuff and improving the activity of the digestive enzymes (Cayan and Erener, 2015). According to our findings, there was no occurrence regarding poultry health disorders, in all dietary treatments because of our rearing environment was thoroughly monitored.…”
Section: Resultsmentioning
confidence: 87%